2006
DOI: 10.2500/ajr.2006.20.2870
|View full text |Cite
|
Sign up to set email alerts
|

Altered Sinonasal Ciliary Dynamics in Chronic Rhinosinusitis

Abstract: Dynamic regulation of respiratory ciliary activity is critical for the respiratory epithelium to adapt to varying environmental situations. Thus, diminished or absent adaptation could predispose the sinonasal cavity to accumulation of inhaled infectious and noxious particulate matter resulting in infection/inflammation. Our findings suggest that CRS patients have decreased sinonasal ciliary adaptation to environmental stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 43 publications
3
69
0
3
Order By: Relevance
“…494 Although there does not seem to be a detectable difference between baseline CBF in CRS patients and control patients, cilia from CRS patients show an attenuated response to substances that reliably increase CBF in controls. 564,565 This blunted response to ciliostimulatory substances may underlie the perpetuation of pathology in CRS. Pathogens such as P. aeruginosa, H. influenzae, Streptococcus pneumoniae, and S. aureus secrete toxins that directly suppress ciliary motion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…494 Although there does not seem to be a detectable difference between baseline CBF in CRS patients and control patients, cilia from CRS patients show an attenuated response to substances that reliably increase CBF in controls. 564,565 This blunted response to ciliostimulatory substances may underlie the perpetuation of pathology in CRS. Pathogens such as P. aeruginosa, H. influenzae, Streptococcus pneumoniae, and S. aureus secrete toxins that directly suppress ciliary motion.…”
Section: Discussionmentioning
confidence: 99%
“…This baseline increase is not observed in CRSsNP explants. 564 Chronically increased CBF has a potential consequence of downregulating endogenous stimulatory pathways, and the cell loses responsiveness to natural CBF stimulants and cannot be modulated normally. 495 Epithelial damage in CRSwNP has also been associated with squamous metaplasia, and abnormal or absent cilia are often associated with this metaplastic change.…”
Section: Viiic1h Crswnp Pathophysiologymentioning
confidence: 99%
“…In addition to direct ciliary loss, cilia surviving the microbial and/or inflammatory insults appear to not function normally. Although the literature is conflicting regarding CBF and its changes in patients with CRS, [49][50][51][52][53] recent work has suggested that a subset of patients with CRS have a blunted ciliary response to environmental stimuli 54 that is reversible once the tissue is removed from the infected or inflamed sinonasal environment. 55 This finding suggests that local exogenous factors can negatively modulate the ciliary dynamic response to stimuli.…”
Section: Acquired Cilia Dysfunctionmentioning
confidence: 99%
“…To understand the need to define chronic sinusitis as a collection of heterogeneous diseases with varying causes. 4. To recognize distinct presentations of chronic sinus diseases, including distinguishing their clinical presentations, cellular and molecular characteristics, genetic differences, and current treatment options for each.…”
mentioning
confidence: 99%